Correlation of CRP Levels with Severity of Disease in Hospitalized Patients with Confirmed COVID-19: Korelasi Kadar CRP dengan Derajat Keparahan Penyakit pada Pasien Rawat Inap Terkonfirmasi COVID-19 - Anisah Wulansari; Rizana Fajrunni'mah; Warida Warida (Ahmar Metastasis Health Journal, 2022)
ABSTRACT Introduction: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by SARS-CoV-2. C-Reactive Protein (CRP) has been found to be an important marker that is significantly altered in severe COVID-19 patients. This study aims to determine the correlation of CRP levels with the agglutination method with the severity of the disease in hospitalized patients who are confirmed positive for COVID-19. This research is an analytic observational with a cross sectional design. The sample is in the form of medical record data of 80 inpatients who are confirmed positive for COVID-19 at Pasar Rebo Hospital for the period August 2020 to January 2021. The data collection process uses a purposive sampling technique. CRP levels (mg/L) were divided into 5 groups, namely <6, 6, 12, 24 and 48. Meanwhile, the severity of the disease was divided into 2 groups, namely mild-moderate and severe-critical. Chi Square statistical test was used to assess the correlation of CRP levels with the severity of the disease. Subjects consisted of 80 confirmed COVID-19 patients with 52.5% male gender more than female (47.5%). Age group 60 years 38.8%, the most compared to other age groups. The severe-critical group 60% more than the mild-moderate (40%). CRP levels <6 mg/L in 17.5% patients, CRP levels 6 mg/L in 3.8% patients, CRP levels 12 mg/L in 27.5% patients, CRP 24 mg/L in 31.3% patients and CRP levels 48 mg/L in 20% patients. The results of the Chi Square test showed a significant correlation between CRP levels and the severity of disease in inpatients confirmed positive for COVID-19 at Pasar Rebo Hospital with a p value of 0.000 at a 95% confidence level. CRP examination can be used as a marker to see the severity of disease in hospitalized patients who are confirmed positive for COVID-19. ABSTRAK Pendahuluan: Coronavirus Disease 2019 (COVID-19) adalah penyakit menular yang disebabkan oleh SARS-CoV-2. C-Reactive Protein (CRP) telah ditemukan sebagai penanda penting yang berubah secara signifikan pada pasien COVID-19 yang parah. Penelitian ini bertujuan untuk mengetahui korelasi kadar CRP metode aglutinasi dengan derajat keparahan penyakit pada  pasien  rawat inap terkonfirmasi positif COVID-19. Penelitian ini adalah observasional analitik dengan desain cross sectional. Sampel berupa data rekam medis 80 pasien rawat inap terkonfirmasi positif COVID-19 di RSUD Pasar Rebo periode Agustus 2020 hingga Januari 2021. Proses pengambilan data dengan teknik purposive sampling. Kadar CRP (mg/L) dibagi dalam 5 kelompok yaitu <6, 6, 12, 24 dan 48. Sementara derajat keparahan penyakit dibagi dalam 2 kelompok yaitu ringan-sedang dan berat-kritis. Uji statistik Chi Square digunakan untuk menilai korelasi kadar CRP dengan derajat keparahan penyakit. Subjek terdiri dari 80 pasien terkonfirmasi COVID-19 dengan jenis kelamin laki-laki 52,5% lebih banyak dibandingkan perempuan 47,5%. Kelompok usia ≥ 60 tahun 38,8% paling banyak dibandingkan kelompok usia yang lain. Kelompok berat-kritis 60%, lebih banyak dibandingkan ringan-sedang 40%. Kadar CRP <6 mg/L sebanyak 17,5% pasien, kadar CRP 6 mg/L sebanyak 3,8% pasien, kadar CRP 12 mg/L sebanyak 27,5% pasien, kadar CRP 24 mg/L sebanyak 31,3% pasien dan kadar CRP 48 mg/L sebanyak 20% pasien. Hasil uji Chi Square didapatkan korelasi yang signifikan antara kadar CRP dengan derajat keparahan penyakit pada pasien rawat inap terkonfirmasi positif COVID-19 di RSUD Pasar Rebo dengan nilai p 0,000 pada tingkat kepercayaan 95%. Pemeriksaan CRP dapat digunakan sebagai salah satu penanda untuk melihat derajat keparahan penyakit pada pasien rawat inap terkonfirmasi positif COVID-19.